PENGARUH KARAKTERISTIK PEKERJAAN KARAKTERISTIK INDIVIDU DAN LINGKUNGAN KERJA NON FISIK TERHADAP KEPUASAN MAHASISWA MAGANG JURUSAN MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS RIAU - Sari Mardila; Hendriani Susi; Fitri Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of work characteristis, individualcharateristic, and nonphysical work environment on the satisfaction of internshipstudents majoring in manajemen faculty of economics and business University ofRiau. The population in this study includes all students majoring in manajemen,who enrolled in the year2017, totaling 201 people. Primary data was collectedusing a questionnaire as an instrument to prove the results of the study, to test thehypothesis in this study, multiple linear regression analysis was used with the helpof SPSS version 26 software. The sampling technique used was ProbabilitySampling or has given every member of the population the opportunity to bechosen into a sample of 135 students majoring in manajemen, who enrolled in theyear 2017. The results of this study indicate that: 1) Work Characteristis has apositive and significant effect on the Satisfaction of Internship Students, 2)Individual Charateristic has a positive and significant effect on the Satisfaction ofInternship Students, 3) Nonphysical Work Environment has a positive andsignificant effect on the Satisfaction of Internship Students 5) WorkCharacteristis, Individual Charateristic, and Nonphysical Work Environment hasa positive and significant effect on the Satisfaction of Internship Students. Keywords: Work Characteristis, Individual Charateristic, Nonphysical WorkEnvironment, Satisfaction of Internship Students.